The Evolutionary Consequences of Blood-Stage Vaccination on the Rodent Malaria Plasmodium chabaudi - Barclay, Victoria C.; Sim, Derek; Chan, Brian H. K.; Nell, Lucas A.; Rabaa, Maia A.; Bell, Andrew S.; Anders, Robin F.; Read, Andrew F. (PLOS Biology, 2012)
A candidate malaria vaccine promoted the evolution of more virulent malaria parasites in mice.